Analisi Butir Soal Pilihan Ganda Pembelajaran Kimia Kelas X SMA Srijaya Negara - Muazarah, Nabilah; Farhan, Muhammad Rafi; Nawawi, Efendi (Jurnal Pendidikan Kimia Universitas Riau, 2025)
This research aimed to analyze the quality of multiple-choice items in chemistry for tenth-grade students at SMA Srijaya Negara based on validity, reliability, difficulty level, and discrimination power. The research method employed was descriptive quantitative. The subjects of the research were 10 multiple-choice questions tested on 26 students. Data were analyzed using Microsoft Excel to calculate validity coefficients, reliability using the Kuder-Richardson 20 (KR-20) method, difficulty level, and discrimination power. The results indicated that 60% of the items were valid; however, the instrument's reliability was low (0.502). The difficulty level of the questions was predominantly in the difficult to very difficult categories (60%), and the discrimination power of the items varied. It was concluded that this evaluation instrument requires significant improvement to enhance its quality as a measurement tool for student learning outcomes.